Asynchronous difference in dynamic characteristics of adsorption swelling and mechanical compression of coal: Modeling and experiments. (November 2020) - Zhao, Wei; Wang, Kai; Liu, Shimin; Ju, Yang; Zhou, Hongwei; Fan, Long; Yang, Yun; Cheng, Yuanping; Zhang, Xiaolei
Abstract: Sorption-induced strain of coal is vital to the prediction of coal bed methane production and stimulation. Previous studies have addressed the relationship between strain and equilibrium pressure and the relationship between strain change and permeability evolution. However, the strain variations with respect to time and the comparison between the asynchronous difference of dynamic characteristics of adsorption swelling and mechanical compression were rarely explored. In this study, we investigated the anisotropy characteristics of strain change over time as well as the influence of the gas species, gas pressure, and pore structure on the dynamic strain variations by using the low temperature liquid nitrogen adsorption method and a self-designed coal strain measurement apparatus. Our results show that gas diffusion rate has a strong influence on sorption-induced strain of coal. Both mechanical compression and sorption-induced strain exhibited an asynchronous effect with respect to saturating time. We then propose a time-depended volumetric deformation model for coal to analyze the mechanism of the asynchronous effect during sorption. This study sheds light on the dynamic process of coal bed methane production and reveals restrictions of current permeability models. Graphical abstract: Image 1